Polymeric Nanocapsule from Silica Nanoparticle@Cross-linked Polymer Nanoparticles via One-Pot Approach - Shen Ruoping (Nanoscale Research Letters, 2009)
Abstract A facile strategy was developed here to prepare cross-linked polymeric nanocapsules (CP nanocapsules) with silica nanoparticles as templates. The silica nanoparticle@cross-linked polymer nanoparticles were prepared by the encapsulation of the silica nanoparticles by the one-pot approach via surface-initiated atom transfer radical polymerization of hydroxyethyl acrylate in the presence ofN,N′-methylenebisacrylamide as a cross-linker from the initiator-modified silica nanoparticles. After the silica nanoparticle templates were etched with hydrofluoric acid, the CP nanocapsules with particle size of about 100 nm were obtained. The strategy developed was confirmed with Fourier transform infrared, thermogravimetric analysis and transmission electron microscopy.